Rise in the Physiological Quality of Seeds of Maize (Zea mays L.) Using Agricultural Bioproducts - Michelle Leiva Arbolaes; Marcos Tulio García González; Marcia María Rodríguez Jauregui; Yander Fernández Cancio (Agrisost, 2019)
Context: One of causes of low yields in maize is the poor physiological quality of the seeds, which does not guarantee populations with the required technical parameters. Nationally, seed germination is fostered with the use of bioproducts in different species.